2020
DOI: 10.1097/bpo.0000000000001639
|View full text |Cite
|
Sign up to set email alerts
|

Pain Control and Medication Use in Children Following Closed Reduction and Percutaneous Pinning of Supracondylar Humerus Fractures: Are We Still Overprescribing Opioids?

Abstract: Background: The purpose of this 2-part study is to determine opioid prescribing patterns and characterize actual opioid use and postoperative pain control in children following discharge after closed reduction and percutaneous pinning of a supracondylar humerus fracture. Methods: A retrospective study was conducted from 2014 to 2016 to determine pain medication prescribing patterns at a single level 1 trauma center. Next, a prospective, observational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 29 publications
7
39
2
Order By: Relevance
“…After the fracture, the limbs were injured, thereby causing damage to the meridians, and the blood flow was not smooth, resulting in swelling of the wound. According to the Golden Book of medical science, the circulation of blood and Qi in the human body was slightly stagnant [ 13 ]. Acupoint massage had the functions of dredging meridians, activating blood circulation and removing blood stasis, and supplementing Qi and detumescence.…”
Section: Related Workmentioning
confidence: 99%
“…After the fracture, the limbs were injured, thereby causing damage to the meridians, and the blood flow was not smooth, resulting in swelling of the wound. According to the Golden Book of medical science, the circulation of blood and Qi in the human body was slightly stagnant [ 13 ]. Acupoint massage had the functions of dredging meridians, activating blood circulation and removing blood stasis, and supplementing Qi and detumescence.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, hydrocodone is the highest single cause of opioid exposure as reported by the National Poison Data System. 12 On the other hand, oxycodone was chosen for 120/126 pediatric patients with supracondylar humerus fracture at a single Level 1 trauma center in a study by Stillwagon et al 13 A report by Monitto et al also found oxycodone to be prescribed most frequently to pediatric surgery patients. 14 These discrepancies demonstrate probable institution-specific prescribing patterns that are necessary to recognize when considering institutional policy changes around opioid medications.…”
Section: Variation In Prescription Typesmentioning
confidence: 99%
“…With proper parental counselling, satisfactory pain control may be achieved with acetaminophen and ibuprofen for most patients. If oxycodone is prescribed for severe pain, the authors recommend its limitation to less than 6 doses [65].…”
Section: "Double-x" Crossed Fixationmentioning
confidence: 99%